Assistance in The Clean And Healthy Living Behavior Program (Phbs) For Vocational High School Students Ma’arif Walisongo Kajoran Magelang - Ahmad Efendi Efendi; Purwanto Purwanto; Yeny Fitriyani; Maryono Maryono; Muhammad Pudail (Institut Riset dan Publikasi Indonesia, 2023)
Schools are a form of educational institution that can be spearheads in improving the community's and students' health status by prioritizing preventive and promotive efforts. Diseases commonly occurring in notable settlements can be prevented and screened from the start so they can be prevented and receive early treatment. Ma'arif Walisongo Kajoran Vocational School emphasizes its students to always behave healthily and cleanly through various methods, one of which is washing their hands. This service aims to assist students in implementing PHBS as an early prevention effort for various diseases. The method used in this service activity is participatory action research or PAR. Based on the results of the activities that have been carried out, all students at Ma'arif Walisongo Kajoran Vocational School are very enthusiastic about implementing PBHS as an effort to prevent various diseases by washing their hands with soap, always wearing masks, keeping the environment clean, exercising regularly, eating nutritious food and other.